High-resolution 2D Raman mapping of mono- and bicomponent filament cross-sections. (16th August 2021) - Perret, E.; Braun, O.; Sharma, K.; Tritsch, S.; Muff, R.; Hufenus, R.
Abstract: A high-resolution Raman mapping method has been developed in order to obtain 2D information about structural anisotropies (crystallinity, molecular alignment) in thin filament cross-sections (diameters between 27 μm and 79 μm). Cross-sections of melt-spun, hot-drawn poly (ethylene terephthalate) (PET) filaments and bicomponent core-sheath PET-polyamide 6 (PA6) filaments have been scanned through a laser beam (spatial resolution <1 μm). Raman spectra were analyzed with a specifically developed peak fitting method to obtain Raman maps, e.g., mapped peak height ratios across the face of the fibers. These maps reveal microscopic interconnected networks of crystalline strands within a low crystalline matrix. Radial gradients in PET crystallinity, as well as average and surface crystallinities, were determined. The presented Raman mapping method to visualize variations in the PET crystallinity across such fine filament cross-sections, and the findings thereof, open a new pathway to better understand how fiber processing parameters affect radial fiber structures. Graphical abstract: Image 1 Highlights: High-resolution Raman mapping of PET filament (diameters 27–79 μm) cross-sections. Novel analysis procedure of Raman maps including peak fitting method. 2D crystallinity and molecular orientation maps of PET filament cross-sections. Correlations between Raman peak height ratios and full width half maxima. Radial gradients and azimuthal structural variations.